The Serum Proteome and Ursodeoxycholic Acid Response in Primary Biliary Cholangitis. Issue 6 (2nd November 2021) - Barron‐Millar, Ben; Ogle, Laura; Mells, George; Flack, Steven; Badrock, Jonathan; Sandford, Richard; Kirby, John; Palmer, Jeremy; Jopson, Laura; Brain, John; Smith, Graham R.; Rushton, Steve; et al.
Abstract : Background and Aims: Stratified therapy has entered clinical practice in primary biliary cholangitis (PBC), with routine use of second‐line therapy in nonresponders to first‐line therapy with ursodeoxycholic acid (UDCA). The mechanism for nonresponse to UDCA remains, however, unclear and we lack mechanistic serum markers. The UK‐PBC study was established to explore the biological basis of UDCA nonresponse in PBC and identify markers to enhance treatment. Approach and Results: Discovery serum proteomics (Olink) with targeted multiplex validation were carried out in 526 subjects from the UK‐PBC cohort and 97 healthy controls. In the discovery phase, untreated PBC patients (n = 68) exhibited an inflammatory proteome that is typically reduced in scale, but not resolved, with UDCA therapy (n = 416 treated patients). Nineteen proteins remained at a significant expression level (defined using stringent criteria) in UDCA‐treated patients, six of them representing a tightly linked profile of chemokines (including CCL20, known to be released by biliary epithelial cells (BECs) undergoing senescence in PBC). All showed significant differential expression between UDCA responders and nonresponders in both the discovery and validation cohorts. A linear discriminant analysis, using serum levels of C‐X‐C motif chemokine ligand 11 and C‐C motif chemokine ligand 20 as markers of responder status, indicated a high level of discrimination with an AUC of 0.91 (CI, 0.83‐0.91). Conclusions: UDCA under‐response in PBC is characterized by elevation of serum chemokines potentially related to cellular senescence and was previously shown to be released by BECs in PBC, suggesting a potential role in the pathogenesis of high‐risk disease. These also have potential for development as biomarkers for identification of high‐risk disease, and their clinical utility as biomarkers should be evaluated further in prospective studies.